2020
DOI: 10.1080/1331677x.2020.1792325
|View full text |Cite
|
Sign up to set email alerts
|

The influence of internal migration on regional innovation in China

Abstract: Based on panel data from 2002 to 2017 in China, this paper analyses the influence of internal migration on regional innovation. The results show that internal migration not only has a significant promoting effect on improving regional innovation, but also presents a significant spatial agglomeration phenomenon. That is, internal migration has a significant positive impact on regional innovation according to the regression without spatial effects. And although internal migration will promote input of regional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this context, migrations not only increase the population of the region but also sometimes have a positive effect on innovation. This situation directly affects the growth potential of regions and is one of the factors recently emphasized in the relationship migration has with interregional imbalance (Zhao & Li, 2020;Freeman, 1997). Migrants consisting primarily of a qualified workforce is found to directly increase innovation (Mare et al, 2011).…”
Section: Literaturementioning
confidence: 99%
“…In this context, migrations not only increase the population of the region but also sometimes have a positive effect on innovation. This situation directly affects the growth potential of regions and is one of the factors recently emphasized in the relationship migration has with interregional imbalance (Zhao & Li, 2020;Freeman, 1997). Migrants consisting primarily of a qualified workforce is found to directly increase innovation (Mare et al, 2011).…”
Section: Literaturementioning
confidence: 99%
“…They share a common characteristic, that is, they usually take place between places that are not distant, between neighbouring units. However, according to [32], internal migration not only increases the region's population, but young people's enthusiasm, self-fulfilment, risk-taking and entrepreneurship will drive innovation and development. At the same time, such migration will bring racial and cultural diversity to cities, fostering integration, while also providing the right conditions for innovation.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by Liao et al [23], who found that work-seeking domestic migration and fertility decisions interplay within the process of economic development, and that migration and fertility rates are higher in less-developed areas than in areas with advanced economies. Domestic migration also promotes regional innovation [24]. Matanle [25] pointed out that the industrialization and urbanization that occurred in Japan throughout the post-World War II era was accompanied by rapid economic growth.…”
Section: Introductionmentioning
confidence: 99%